Respuesta :

The simplified form of the expression is -106

Simplifying an expression

From the question, we are to simplify the given expression

The given expression is

4⁰ + 9 x 2 – 5³

Simplifying

4⁰ + 9 x 2 – 5³

First, evaluate the exponents

5³ = 125

4⁰ = 1

Thus, the expression becomes

1 + 9 x 2 – 125

Simplifying further

1 + 18 - 125

= 19 - 125

= -106

Hence, the simplified form of the expression is -106

Learn more on Simplifying an expression here: https://brainly.com/question/19284077

#SPJ1